2010
DOI: 10.1111/j.1600-0501.2009.01875.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone substitute as an on‐lay graft on rat tibia

Abstract: Cerament may guide bone generation from an intact cortical bone surface. Although bone remodeling speed may differ between rats and humans, our study indicates that Cerament may become a useful alternative to autologous bone, both to fill defects and to increase bone volume by cortical augmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Different sites are used to evaluate the bone healing of defects created in rats, such as tibia (Melo et al 2005; Ribeiro et al 2008; Truedsson et al 2010), calvaria (Furlaneto et al 2007; Messora et al 2008; Nagata et al 2010), and jaws (Ebina et al 2009; Schliephake et al 2009). Rat tibia was chosen to try to keep the materials in contact with bone tissue, representing similar condition to that in which the bone grafts are normally employed in human beings (Howard & Kelley 1969; Truedsson et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Different sites are used to evaluate the bone healing of defects created in rats, such as tibia (Melo et al 2005; Ribeiro et al 2008; Truedsson et al 2010), calvaria (Furlaneto et al 2007; Messora et al 2008; Nagata et al 2010), and jaws (Ebina et al 2009; Schliephake et al 2009). Rat tibia was chosen to try to keep the materials in contact with bone tissue, representing similar condition to that in which the bone grafts are normally employed in human beings (Howard & Kelley 1969; Truedsson et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, IBSs are injected into the implantation site, followed by the placement of titanium screws before hardening in situ . Alternatively, IBSs can be placed around the screws after screw implantation in order to investigate the ability of an IBS to increase the bone mass on a cortical bone surface and to study the pattern of bone remodelling in, and adjacent to, the bone substitute (Truedsson et al ., ). The number of implants that can be placed in metaphyseal bones differs between animal species and defect site: two implants (one per site) in the rat femoral condyle (Yu et al ., ) and in the rat and rabbit proximal tibia (Kawagoe et al ., ); two implants into each goat femoral condyle (Ooms et al ., ); and up to three implants in each dog proximal tibia (Arisan et al ., ).…”
Section: Epiphysis and Metaphysis Of Long Bonesmentioning
confidence: 97%
“…Jensen et al concluded in an experimental study, that the amount of bone formation was inversely proportional to the HA/TCP ratio [16]. CERAMENT™|BONE VOID FILLER used in an intraoral environment has the proposed capacity to guide bone generation from a surface of intact cortical bone [17]. There were only 60% of the Tigran cases which showed complete re-establishment of the buccal cortical defect, which can be explained by that Tigran granules may need a longer healing period like in CERA-MENT™|BONE VOID FILLER.…”
Section: Discussionmentioning
confidence: 99%